Effect of Particle Shape on Repose Angle Based on Hopper Flow Test and Discrete Element Method - Jian-Jun Fu; Cheng Chen; Jean-Francois Ferellec; Juan Yang (Advances in Civil Engineering)
The repose angle of granular material is an essential parameter to understand the microbehavior of the granular material and, then, to relate it with the macrobehavior. In this study, a self-design large-scale hopper flow test apparatus has been developed to measure the repose angle of the ballast using a fixed funnel method. Then, the numerical simulation using the realistic clump is compared with the experimental test to prove its validity. Meanwhile, the idealized clumps with custom shape parameters, including roughness of particle and ground, angularity, aspect ratio, and sphericity, were chosen to analyze the influences of particle shape on the repose angle. The results show that the angle of repose generally tends to increase with the increase of the friction coefficient of particles and the roughness of the ground. With the increase of the angularity from 0 to 4, the pile height and the repose angle increase. Meanwhile, the extended area decreases accordingly. For cuboid particles, with aspect ratio increasing from 1.0 to 1.67, the angle of repose increases firstly and then maintains a constant between aspect ratio 1.25–1.67. For ellipsoid particles, the angle of repose decreases, then reaches a minimum at aspect ratio around 1.3, and finally increases.